Endophytic entomopathogenic fungi negatively impact on growth and development of Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) - Herlinda, Siti; Milinia Puspita Sari, Jelly; Elfita, .; Suwandi, Suwandi; Anggraini, Erise; Hong Lau, Wei; Arrwais, Rhani; Irsan, Chandra; Hamidson, Harman; Hasyim, Hamzah; Verawaty, Marieska (Bogor Agricultural University, 2025)
An alternative method for controlling Spodoptera frugiperda applies entomopathogenic fungi (EPF). The present research aimed to determine the impact of the endophytic EPF on the growth and development of S. frugiperda. Twenty molecularly identified isolates of the endophytic EPF were used in seed treatments with the fungal suspension 1 × 1010 conidia.mL-1. The endophytic EPF that colonized corn leaves eaten by the neonate S. frugiperda larvae was able to significantly decrease the body weight of the larvae and pupae. The endophytic EPF could prolong the developmental time of all instar larvae and pupae. The endophytic EPF could raise larval and pupal mortality and reduce the ability of adults to emerge from pupae, and decrease egg laying by females. The lowest percentage of adult emergence was observed in the adults from larvae consuming corn leaves colonized with Beauveria bassiana JaGiP and JgSPK isolates, which were 34.67% and 24%, respectively. Consequently, a reduced adult emergence could lead to a high cumulative death rate of 76% from larvae to adults. Finally, the endophytic EPFs negatively affect S. frugiperda growth and development. B. bassiana JaGiP and JgSPK isolates are the most pathogenic fungi in inhibiting the growth and development of S. frugiperda. They are promising candidates for controlling S. frugiperda in the corn field.